The rebirth of the church : applying Paul's vision for ministry in our post-Christian world - Gibbs, Eddie (Grand Rapids, MI Baker Academic, 2013)
"Churches across the Western world have become increasingly fragmented and marginalized, often struggling to survive. Here Eddie Gibbs, a bestselling author and veteran church and culture expert, addresses the challenges of re-imagining the church in a post-Christian world. He gleans critical biblical insights from the early church's experience to help contemporary leaders and churches minister more effectively. Gibbs compares and contrasts the social and cultural context of the twenty-first century with the first century, exploring what can be learned about the birthing of churches in the book of Acts and in Paul's letters. He identifies the issues Paul faced in order to sustain a movement growing exponentially and considers what lessons might be learned in addressing current challenges in the church. The book examines vital issues not only for the survival of the church but also for its revitalization and rebirth, and provides direction for local churches on becoming agents of mission." -- Publisher description.
Part 1. Comparing contexts. Engaging twenty-first-century post-Christendom contexts -- Engaging first-century contexts -- Part 2. Issues and insights. Urban engagement -- Birthing new churches -- Caring for new churches -- Welcoming and incorporating new members into the body of Christ -- Upholding the apostolic message -- Relationships within the church and with the world -- Mission and ministry, then and now.
Includes bibliographical references and index.
Keywords: Bible. -- Theology; Church renewal; Church development, New; Evangelistic work